Methodological Basis for Mapping the Consequences of Military Soil Degradation at the Level of the Territorial Community - Solovei, V. B.; Zalavskyi, Yu. V.; Lebed, V. V.; Solokha, M. O.; Kucher, A. V. (Ukrainian Geographical Journal, 2024)
The purpose of this study is to develop a set of digital maps of the pre-war and current state of soil resources at the territorial community level based on the proposed methodological approaches (on the example of the Chkalovska territorial community (hromada) of the Chuguyiv district of the Kharkiv region). We used the following primary methods: comparative-geographical, statistical, relief plasticity, cartographic, geostatistical, and graphic. Maps of the qualitative state and distribution of the leading quantitative indicators of soils in the Chkalovska community based on pre-war data were created. Based on the remote research results on the impact of military actions on the quality of chernozems in the Chkalovska community, types (mechanical, biological) and kinds (aviation and artillery craters, military roads, vegetation burning, anti-tank ditches, support points/trenches) of soil cover damage, and their scales (areas). A map of military soil degradation was developed with GIS by overlaying the contours of the most intensively damaged soil cover on a geographic base. A map scheme of mined and cleared agricultural lands, areas undergoing demining, and the structure of the cultivated fields’ sown areas has been constructed as the basis for forming a network for soil sampling within the community. An online map was created by uploading data layers to the ArcGIS Online platform. Almost the entire territory of the Chkalovska community has suffered some degree of damage from the armed aggression of the russian federation. The most damaged due to hostilities are the most fertile soils of the Chkalovska community—typical heavy loam and light clay chernozems. The feasibility of using the developed digital mapping algorithm, based on map versions, to determine the qualitative state of the soil cover and the spread of areas of soil damage resulting from hostilities at the level of territorial communities has been determined. The developed soil cartographic materials will serve as the basis for effective management decisions regarding post-war soil recovery.